Pengaruh Variasi Komposisi Antara Limbah Plastik High Density Polyethylene (HDPE) Dan Abu Dasar Batubara Sebagai Material Komposit Dengan Matrik Semen Terhadap Kekuatan Tekan Dan Serapan Air - Muttaqim, Zaennal, Dr. Agus Dwi Anggono (2017)
Garbage is a serious problem in every develop country both of organic and inorganic waste. The examples of inorganic waste are plastics, coal ash, iron, tin and others. It were difficult to recycle naturally or to degrade itself. Plastic is one type of inorganic waste that is not all of these types of materials can be recycled. This study was conducted to reduce waste, especially plastic waste of HDPE (high density polyethylene). Cement was selected as an adhesive and coal bottom ash as an additive. In the research, three components will be used to develop a new positematerials.The standard reference of this research is SNI ( (Indonesian National Standard). SNI-03-6825-2002 was used for ompressive strength testing and SNI 03-0349-1989 was selected for water absorbtion experiment. The size of the specimen was 5x5x5 cm. The ratio of HDPE:coal bottom ash was varied as 70%: 0%, 60%: 10%, 50%: 20% and 40%: 30%. The Holcim cement used 30% of the volume fraction. The testing was performed after 7 days and 28 days dried specimens. From the test results, it was obtained that the age of 7 days specimen was delivered the compressive strength of 5.884 N / mm2 in a ratio of 50%: 20%. For the 28 days specimen, it has compressive strength of 8.134 N / mm2. The water absorbtion was porpotional with the coal bottom ash. The lowest water absorbtion was given by ratio of 40%: 30% as 16.971%. Another measurement was done for volume weight of the specimens. It was delivered 1.076 gr / cm3 as average.